Improving understanding of music therapy with a non-verbal child: sharing perceptions with other professionals : a research presented in partial fulfilment of the requirements for the Master of Music Therapy at New Zealand School of Music, Wellington, New Zealand - Park, Yaeun Kyung (Massey University, 2008)
This study explored the value of music therapy practice with a non-verbal child conducted by the author, a Music Therapy Student (MTS), as seen through the eyes of two music therapists and the child’s mother, as well as the improvement achieved in the MTS’s understanding of music therapy practice through sharing the three professionals’ insights. The paper addresses two research questions: (1) How is music therapy with a non-verbal child perceived by music therapy professionals? (2) How does sharing these professionals’ understanding of music therapy improve the MTS’s understanding of this therapeutic process? The MTS’s self-reflections were treated as part of the data in this research, as was the non-verbal communication within the music therapy intervention to support the findings. The qualitative research, ‘Naturalistic inquiry’ was used for this research. Data was collected by interviewing these three professionals individually about their perceptions of music therapy after watching three video extracts of normal music therapy sessions with the child. The video extracts were selected from the significant moments of non-verbal communication. Through this process of sharing the professionals’ perceptions, the MTS gained a deeper understanding of both the child and the music therapy practice administered, confirming and extending her understanding of the musical and therapeutic skills and techniques of the three professionals, which they had gained in their varied experiences and which had been shaped by their varied backgrounds. The MTS was thus engaged in a learning process which hoped would enhance the quality of therapy provided by her in the future.
Keywords: Music therapy professionals; Perception; Music therapy practice; Fields of Research::410000 The Arts::410100 Performing Arts Studies::410101 Music studies